1992
DOI: 10.1056/nejm199204233261702
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in the Use of Breast-Conserving Treatment for Breast Cancer

Abstract: There is substantial geographic variation in the use of breast-conserving surgery, which cannot be explained by differences in hospital characteristics. Hospital characteristics that were independently redictive of greater use of breast-conserving surgery were the size of the metropolitan area, the status of the institution as a teaching hospital, and the availability of radiation therapy and geriatric services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
292
1
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(306 citation statements)
references
References 17 publications
12
292
1
1
Order By: Relevance
“…These data extend findings from previous research demonstrating that black women may receive less aggressive treatment for their breast carcinomas than whites 39 -43 and that racial differences in treatment often persist after control for sociodemographic factors. 39,40,43 Our findings also suggest that black women may have different experiences in receiving care for their breast carcinoma than whites. This idea is supported by the result that blacks perceived more racism and ageism in the health care system than whites.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These data extend findings from previous research demonstrating that black women may receive less aggressive treatment for their breast carcinomas than whites 39 -43 and that racial differences in treatment often persist after control for sociodemographic factors. 39,40,43 Our findings also suggest that black women may have different experiences in receiving care for their breast carcinoma than whites. This idea is supported by the result that blacks perceived more racism and ageism in the health care system than whites.…”
Section: Discussionmentioning
confidence: 54%
“…However, given the substantial increase in breast conservation rates over time, 39,41,47 a larger absolute number of black women could be at risk for undertreatment if the observed magnitude of race effects persist and are experienced across the entire population. 61 Because Medicare does not collect data on SES, area-level measures were used as a proxy for individual data.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, rates of BCT in the 1980s ranged from 3.5% to 21.2% across the United States. 12 Even as recently as 1995, the use of mastectomy in the elderly was found to vary by 4.7-fold across hospital referral regions, from 0.91 per 1000…”
Section: Discussionmentioning
confidence: 99%
“…However, we did find markedly increased rates of BCT in the elderly using the same population and methods as previous studies. 10,12 Therefore, stage should not be a significant confounder. The association between socioeconomic status and BCT use could be confounded by disease stage.…”
Section: Limitationsmentioning
confidence: 99%
“…Two randomized trials published in the mid-1980s demonstrated that breast-conserving surgery (hereinafter referred to as lumpectomy) plus whole-breast RT provided equivalent survival benefits while improving the cosmetic effects and quality of life for the patient. 1,2 Nattinger et al 3 and Farrow et al 4 demonstrated that, within a few years, the use of lumpectomy among U.S. women increased rapidly. With a higher usage of screening mammography and with a downward shift in the stage distribution of newly diagnosed breast carcinoma cases, the choice of the more limited surgical approach has increased even further.…”
mentioning
confidence: 99%